Modal Analysis of a Cantilever Beam with Various Material Using ANSYS - Maj, Dana; Dr. Zaleha Binti Mohamad, (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The purpose of this research is to examine the vibration characteristics of a cantilever beam under various fracture surfaces and materials. The goals include employing Finite Element Analysis (FEA) software to explore the influence of different fracture sites along the beam on its vibration responses. The investigation also aims to detect fracture severity levels in the system. The Finite Element Analysis provides vital information on the dynamic behaviour of the cantilever beam. In terms of natural frequency and mode shape, the results show that mild steel surpasses aluminium and stainless steel. The comparison research emphasises material-dependent changes in vibration characteristics, emphasising the relevance of material selection in robust structure design. This study advances the field by giving a thorough understanding of how different fracture surfaces and materials affect the vibration responses of cantilever beams. The findings have practical relevance for structural engineers and researchers involved in mechanical system design and assessment, providing vital insights for optimising structure performance and durability under diverse situations.